Progressıve Web Apps : A Development And Acceptance Study Among College Students In Indonesıa Usıng Scrum Framework And Utaut Model - Herman Herman; Frederick Frederick (Universitas Internasional Batam, 2023)
Currently, the usage of mobile applications and the total activity on mobile phones through web browsing or native applications is very high. But both have limitations. In web applications, the user experience that users receive is not that great compared to native applications, and on mobile native applications, it requires higher development costs to ensure the app is able to be accessed across multiple platforms. To solve this problem, Google launched the progressive web apps as an alternative, where progressive web apps can be accessed through various different platforms, saving development costs but still providing a user experience that is almost the same as native apps. The focus of this research is to develop a progressive web app with React.js using the scrum method, and also to do research about user acceptance of progressive web apps through qualitative methods/interviews based on the UTAUT research model to students and lecturers of computer science in general. The result of this research, which is based on UTAUT points, shows responses toward the acceptance of progressive web apps that are represented in the form of affinity diagram. With this research, it is hoped that it can bring benefits to the decision to use the progressive web apps, become a reference for the next research, and increase the knowledge of the public and readers about the progressive web apps.